Реформација и Света Гора Атонска – једно српско сведочанство - Špadijer, Irena (Slavia Centralis, 2020)
Mount Athos has been the most specific monastic community in Europe for over a thousand years. Though isolated from the rest of the world, the community has always reflected the turning points in European history, including Reformation. The paper looks at one testimony of this kind – the Epistle of the protos Gavrilo Svetogorac (Gavrilo from Mount Athos) to John Zapolya, Hungarian king, written probably in 1533/1534. Gavrilo from Mount Athos was an Eastern Orthodox Church monk who was mentioned many times and in different sources as a translator from Greek into Serbian. At the time of his correspondence with the Hungarian ruler he was a protos ‒ the head of Mount Athos. At the request of John Zapolya, Gavrilo offers his opinion about Martin Luther as well as his view on certain events in the history of the Catholic Churc Judging by the time when the epistle was written, and the attitudes expressed in it, the protos of Mount Athos was actively involved in the events in Europe in that particular period.
Keywords: Reformation and Athos; Gavrilo from Mount Athos; John Zapolya; Martin Luther